ANALYSIS OF NONMUSLIM COMMUNITY INTEREST IN USING BANK SYARIAH INDONESIA SAVINGS PRODUCTS IN DELI SERDANG - Dedek Joefanny; Nurul Inayah; Nursantri Yanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Islamic banks are often assumed to only serve Muslims, when in fact, non-Muslims also show interest in using Islamic banking services such as BSI savings products, to store their funds. This study aims to examine the interest of non-Muslims in BSI savings by focusing on location, product, and promotion factors. Using the accidental sampling method, and using primary and secondary data sources, primary data was collected through interviews with respondents, while secondary data came from the Central Statistics Agency and literature studies. The results of the study show that the three factors such as location, product, and promotion show that the location, product, and promotion factors have a significant effect on the interest of non-Muslims in using BSI savings products, and from the results of the study, it is found that the interest of non-Muslim people is still categorized as low with an indicator of <50% to save at Bank Syariah Indonesia.